Memaknai Pandemi Covid-19 Di Dalam Kerangka Providentia Dei - Tombeng, Ineke (Educatio Christi, 2022)
Covid-19 is a pandemic that first emerged in Wuhan, China at the end of 2019. The emergence of this pandemic of course raises anxiety and raises many questions. One of them is about the presence of God in the midst of this pandemic situation. This paper seeks to deal with the Covid-19 pandemic within the framework of Providentia Dei, namely the Christian doctrine of God's providence. The fundamental issue that becomes the focus of writing is how to understand God the Creator and Sustainer in the midst of the current pandemic? In order to answer this question, I am exploring the causes and views of the church on the four pandemics in world history. The results of this historical search are then understood from five perceptions of the pandemic, namely fate, punishment for sins, tests of faith, and signs of the End Times. Next is trying to understand the Covid-19 pandemic within the framework of Providentia Dei, which, in my opinion, must be understood in the light of the Cross as a manifestation of God's providence as "a vulnerable God," "suffering God," and "God who restores."